Dam Operations Affect Route‐specific Passage and Survival of Juvenile Chinook Salmon at a Main‐stem Diversion dam. (15th July 2016) - Perry, R. W.; Kock, T. J.; Courter, I. I.; Garrison, T. M.; Hubble, J. D.; Child, D. B.
Abstract: Diversion dams can negatively affect emigrating juvenile salmon populations because fish must pass through the impounded river created by the dam, negotiate a passage route at the dam and then emigrate through a riverine reach that has been affected by reduced river discharge. To quantify the effects of a main‐stem diversion dam on juvenile Chinook salmon in the Yakima River, Washington, USA, we used radio telemetry to understand how dam operations and river discharge in the 18‐km reach downstream of the dam affected route‐specific passage and survival. We found evidence of direct mortality associated with dam passage and indirect mortality associated with migration through the reach below the dam. Survival of fish passing over a surface spill gate (the west gate) was positively related to river discharge, and survival was similar for fish released below the dam, suggesting that passage via this route caused little additional mortality. However, survival of fish that passed under a sub‐surface spill gate (the east gate) was considerably lower than survival of fish released downstream of the dam, with the difference in survival decreasing as river discharge increased. The probability of fish passing the dam via three available routes was strongly influenced by dam operations, with passage through the juvenile fish bypass and the east gate increasing with discharge through those routes. By simulating daily passage and route‐specific survival, we show that variation in total survival is driven by river discharge and moderated by the proportion of fish passing through low‐survival or high‐survival passage routes. Copyright © 2016 John Wiley & Sons, Ltd.